Selecting efficient treatments to phytoremediate nitrate contamination in well water, ex- situ, using Ipomoea aquatic - Tharmarasa, H.; Jeyakumar, K.; Sivagnanasegaram, K.; Gnanavelrajah, N. (Faculty of Agriculture, University of Ruhuna, Sri Lanka., 2022)
Overuse of nitrogen fertilizer leads to excess nitrate in soils and it leached through the soil profile and accumulates with groundwater. More than 10mg/l NO3- - N or 50 mg/l NO3- (WHO, 2011) causes a serious problem for all living beings to depend on groundwater. Phytoremediation is a cheaper, economically viable, and eco-friendly method to remove nitrate contamination. Considering these a study was conducted to assess the feasibility of using Ipomoea aquatica to reduce nitrate in groundwater. Samples were collected from nitrate contamination well in the Chunnakam aquifer and analyzed for nitrate and some chemical properties. The experiment was conducted in a three-factor factorial design with the factors of numbers of plant (5 and 10), the water application method (without refill up to initial mark at the weekly interval and with refill up to initial mark at weekly interval), and foliar fertilizer application method (without use foliar fertilizer and use foliar fertilizer) with three replicates. Treatments were, T1- 5plants alone, T2- 5 plants + fertilizer, T3-10 plants alone, T4- 10 plants + fertilizer, T5- 5 pants + refill, T6- 5 pants + refill + fertilizer, T7- 10 pants + refill, T8- 10 pants + refill + fertilizer. 3.7 liter of water was initially used and continued up to 3rd week. Nitrate was analyzed for initial and weekly intervals and pH, EC, total hardness, SO42-, PO43-, Fe2+, Cl- and TDS were analyzed initially and at the end. Plant NO3--N, chlorophyll, total phosphorus, potassium, fresh and dry weight were analyzed after harvesting. Initial nitrate, pH, EC, Total hardness, SO42-, Cl-, PO43-, Fe2+ and TDS were 138 mg/l, 7.79, 0.93 mS/cm, 212 mg/l, 111.82 mg/l, 272.17 mg/l, 0.03 mg/l, 0.37 mg/l, 823.33 mg/l respectively. Among the treatments, 10 plants treatments were removed significantly higher nitrate, below the safe level. However, the available water at the end was the lowest in T3 and T4. But T7 and T8 had the initial amount of remediated water. All the treatments were reduced the initial level of water properties. NO3- reduction in water and NO3--N accumulation in plants were high in T8 which was recorded as 55.84 mg/kg in water spinach. 100g contains 5.58 mg of nitrate. This phyto-remediated Ipomoea aquatica could be used as a vegetable even for infants without any harmful effect. It can be concluded that this method could be used by households to treat nitrate polluted well water while getting fresh leafy vegetables.
Keywords: Groundwater; Ipomoea aquatica; Nitrate; Phytoremediation